2018
DOI: 10.25311/keskom.vol4.iss2.184
|View full text |Cite
|
Sign up to set email alerts
|

Pelaksanaan Program Deteksi Dini Kanker Cerviks (Ca Cervix) dengan Metode Inspeksi Visual Asam Asetat (IVA) di Kabupaten Kampar

Abstract: ABSTRAK Pelaksanaan program deteksi dini kanker serviks dengan metode IVA merupakan kebijakan pemerintah Republik Indonesia dalam upaya mengantisipasi dan menurunkan angka kejadian kanker serviks. Masih rendahnya cakupan deteksi dini kanker serviks pada tahun 2016 di Kabupaten Kampar yaitu hanya 1.165 orang wanita usia subur (wus) dari jumlah sasaran 110.236 orang atau hanya 6% dari target 100%. Tujuan penelitian ini adalah untuk mengetahui bagaimana pelaksanaan program deteksi dini kanker serviks dengan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
5
0
2
Order By: Relevance
“…The source of funds comes from the APBN and APBD, but the largest source comes from BOK funds ( Health Operational Assistance). Similarly, Rahayu et al (2018) also show that the implementation of the IVA test comes from BOK and JKN funds (Rahayu, et al, 2018).…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…The source of funds comes from the APBN and APBD, but the largest source comes from BOK funds ( Health Operational Assistance). Similarly, Rahayu et al (2018) also show that the implementation of the IVA test comes from BOK and JKN funds (Rahayu, et al, 2018).…”
Section: Discussionmentioning
confidence: 91%
“…Research conducted by Ridwan (2020) also found that the facilities at the Sei Lekop health center had passed PMK 34/2015 standards, while infrastructure still does not (Ridwan,2020). Even so, there are health centers that still have facilities and infrastructure inadequate in carrying out IVA test services, for example, those found in Kampar Regency (Rahayu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations